Multi-Functional Access to Justice Centres - Afilalo, Nathan; Escott, Daniel; Zariski, Archie (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2024)
In recent years, the integration of digital technology into the Canadian judicial system has accelerated, driven by both technological advancements and the urgent needs highlighted by the COVID-19 pandemic. This article explores the transformative potential of digital justice within Canadian courts, focusing on a proposal to repurpose circuit court facilities as "Access to Justice Centres" [AJCs]. These centers aim to address existing access to justice issues by providing state-of-the-art digital interfaces and centralizing court functions while preserving the dignity and decorum of in-person proceedings. Our analysis evaluates the successes and challenges of digital technologies in judicial processes, informed by empirical research with Canadian judges. The findings suggest that while digital tools have enhanced judicial efficiency and access to justice, significant disparities remain, particularly for marginalized communities. By leveraging user-centric design principles and existing infrastructure, AJCs could offer innovative solutions to bridge these gaps, ensuring that digital justice benefits all sectors of society. This article contributes to the ongoing dialogue on judicial reform, emphasizing the need for a thoughtful and inclusive approach to integrating technology in the administration of justice.